2000
DOI: 10.1002/1097-0142(20000715)89:2<314::aid-cncr16>3.0.co;2-v
|View full text |Cite
|
Sign up to set email alerts
|

Survival advantage of combined chemoradiotherapy compared with resection as the initial treatment of patients with regional pancreatic carcinoma

Abstract: BACKGROUND Resection of pancreatic carcinoma is resource‐intensive with a limited impact on survival. Chemotherapy and/or radiotherapy (RT) have been shown to be effective palliation. To examine whether preoperative chemoradiotherapy as the initial treatment improves survival for patients with a regional pancreatic adenocarcinoma with a minimal chance of being resected successfully, an outcomes trial was conducted. METHODS Patients with radiologically regional tumors were staged by laparotomy and/or computed t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

4
89
0
8

Year Published

2003
2003
2015
2015

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 187 publications
(101 citation statements)
references
References 35 publications
(91 reference statements)
4
89
0
8
Order By: Relevance
“…The median survival time of patients with objective response (CR þ PR), SD, and PD were 18.3, 16.7, and 7.5 months, respectively. chemoradiotherapy, potentially allowing the patient to expect long-term survival after curative resection (Snady et al, 2000;Ammori et al, 2003). In a chemoradiotherapeutic setting, the chemotherapeutic agent should be a potent radiosensitiser to maximise the therapeutic gain of radiotherapy on primary tumours and have a systemic cytotoxicity to reduce the early metastasis of pancreatic cancer (Moertel et al, 1981;Blackstock et al, 1999).…”
Section: Discussionmentioning
confidence: 99%
“…The median survival time of patients with objective response (CR þ PR), SD, and PD were 18.3, 16.7, and 7.5 months, respectively. chemoradiotherapy, potentially allowing the patient to expect long-term survival after curative resection (Snady et al, 2000;Ammori et al, 2003). In a chemoradiotherapeutic setting, the chemotherapeutic agent should be a potent radiosensitiser to maximise the therapeutic gain of radiotherapy on primary tumours and have a systemic cytotoxicity to reduce the early metastasis of pancreatic cancer (Moertel et al, 1981;Blackstock et al, 1999).…”
Section: Discussionmentioning
confidence: 99%
“…We suggest that a neoadjuvant approach should be preferred and should include gemcitabine-based chemotherapy and radiation therapy. This makes sense, particularly since delayed recovery after surgery precludes adjuvant therapy in approximately 30% of patients who undergo elective PD as the initial treatment for pancreatic adenocarcinoma 29,30 . However, the best neoadjuvant regimen is still to be determined 31 .…”
Section: Future Strategiesmentioning
confidence: 99%
“…Snady et al reported a median survival of 23.6 months in 68 patients with locally invasive 'unresectable' pancreatic adenocarcinoma who had preoperative chemoradiotherapy (split-course radiotherapy plus 5-FU, streptozocin and CDDP), whilst 91 other patients who underwent a resection had a median survival of only 14 months. 176 In the latter resection group, 63 patients received post-operative chemotherapy or chemoradiotherapy with a median survival of 16 months compared to 11 months in those who had resection without further treatment. 176 Magnin et al…”
Section: Adjuvant and Neo-adjuvant Chemoradiotherapymentioning
confidence: 99%
“…176 In the latter resection group, 63 patients received post-operative chemotherapy or chemoradiotherapy with a median survival of 16 months compared to 11 months in those who had resection without further treatment. 176 Magnin et al…”
Section: Adjuvant and Neo-adjuvant Chemoradiotherapymentioning
confidence: 99%